1984
DOI: 10.1111/j.1600-0587.1984.tb01143.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth, maturation and survival of frogs Rana temporaria L.

Abstract: A total of 1560 breeding frogs were collected in three consecutive years at sites in the west of Ireland. Alt were weighed and measured and the ages of 702 individuals were determined by skeletochronology. The length‐weight relationship differed between gravid females, spent females and males, with the gravid females showing the largest weight gain for any increase in length. The majority of males bred for the first time at two years, but most females delayed maturity until they were a year older. While the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 12 publications
3
49
0
Order By: Relevance
“…In anuran species, Monnet & Cherry (2002) found that the sexual dimorphism in body size indicated different survival rates in males and females. A difference between male and female survival was found in species of the genus Desmognathus (Tilley 1980), in the Columbian spotted frog Rana lut ei ven tris (Turner 1960) and the common frog Rana temporaria (Gibbons & McCarthy 1984). However, our results based on local survival indicated that the average lifespan was similar for both sexes, confirming previous re sults from Pinya & Pérez-Mellado (2013).…”
Section: Discussionsupporting
confidence: 87%
“…In anuran species, Monnet & Cherry (2002) found that the sexual dimorphism in body size indicated different survival rates in males and females. A difference between male and female survival was found in species of the genus Desmognathus (Tilley 1980), in the Columbian spotted frog Rana lut ei ven tris (Turner 1960) and the common frog Rana temporaria (Gibbons & McCarthy 1984). However, our results based on local survival indicated that the average lifespan was similar for both sexes, confirming previous re sults from Pinya & Pérez-Mellado (2013).…”
Section: Discussionsupporting
confidence: 87%
“…However, in a few species positive correlations between body size and age are determined either only for males (B. pardalis, Cherry & Francillon 1992) or only for females (R. temporaria, Gibbons & McCarthy 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Another process that may result in a malebiased adult sex ratio is that female anurans often mature later than males (Berven, 1990 (R. sylvatica); Gibbons and McCarthy, 1984;Reading, 1991 (B. bufo) ;Miaud, Guyétant and Elmberg, 1999 (R. temporaria)). …”
Section: Introductionmentioning
confidence: 99%